Sea of glory : America's voyage of discovery : the U.S. Exploring Expedition, 1838-1842 - Philbrick, Nathaniel (New York : Viking, 2003)
In 1838, the U.S. government launched the largest discovery voyage the Western world had ever seen-6 sailing vessels and 346 men bound for the waters of the Pacific Ocean. Four years later, the U.S. Exploring Expedition returned with an astounding array of accomplishments and discoveries: 87,000 miles logged, 280 Pacific islands surveyed, 4,000 zoological specimens collected, including 2,000 new species, and the discovery of the continent of Antarctica. And yet at a human level, the project was a disaster-not only had 28 men died and 2 ships been lost, but a series of sensational courts-martial had also ensued that pitted the expedition's controversial leader, Lieutenant Charles Wilkes, against almost every officer under his command. Though comparable in importance and breadth of success to the Lewis and Clark Expedition, the Ex. Ex. has been largely forgotten. Now, Nathaniel Philbrick re-creates this chapter of American maritime history in all its triumph and scandal. Sea of glory combines meticulous history with spellbinding human drama as it circles the globe from the palm-fringed beaches of the South Pacific to the treacherous waters off Antarctica and to the stunning beauty of the Pacific Northwest, and, finally, to a court-martial aboard a ship of the line anchored off New York City.
Young ambition -- The Great South Sea -- The deplorable expedition -- Most glorious hopes -- At sea -- The turning point -- Commodore of the Pacific -- Antarctica -- A new continent --- The cannibal isles -- Massacre at Mololo -- Mauna Loa -- The wreck of the Peacock -- Homeward bound -- Reckoning -- This thing called science -- Legacy.
Includes bibliographical references (pages 415-436) and index.
Keywords: Ethnological expeditions -- History -- 19th century; Ethnology -- United States -- History -- 19th century; Ethnology -- Oceania -- History -- 19th century; Wilkes, Charles, -- 1798-1877.; Wilkes, Charles, -- 1798-1877; Ethnological expeditions; Ethnology; Oceania; United States; Ontdekkingsreizen; Geschichte 1838-1842.; Expedition; USA; Ozeanien; 1800 - 1899; History